Haida village with totem poles and canoes, Howkan village, Long Island, Alaska, ca. 1888 - De Groff, Edward
Haida village, ca. 1886-1890. A number of wooden houses and buildings set off beach; totem poles ring the houses, canoes are pulled up onto beach. Several Haidas can be seen off to side. Notes from unidentified sources: Indian village, Howkan, Southwest Alaska